1980
DOI: 10.1577/1548-8659(1980)109<632:ctmoft>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thermal Maxima of Five Trout Species in the Southwestern United States

Abstract: Critical thermal maxima (CTM) and responses to fluctuating thermal regimes indicate that adult rainbow (Salmo gairdneri), brown (Salmo trutta), and brook (Salvelinus fontinalis) trout species, introduced into the southwestern United States, are as well adapted to elevated water temperature as adult Gila (Salmo gilae) and Arizona (Salmo apache) trout, which are native to that region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
3
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 5 publications
7
82
3
2
Order By: Relevance
“…Shifts in water temperature outside of that preferred thermal range can adversely affect the overall health of the aquatic ecosystem. High water temperatures in the range of 23-25°C have been shown to increase the mortality rates of a number of fish species (Lee and Rinne, 1980;Bjorn and Reiser, 1991;Hodgson and Quinn, 2002). Lund et al (2002) showed high summer water temperatures to be the cause of a heat-shock response in juvenile salmonids.…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in water temperature outside of that preferred thermal range can adversely affect the overall health of the aquatic ecosystem. High water temperatures in the range of 23-25°C have been shown to increase the mortality rates of a number of fish species (Lee and Rinne, 1980;Bjorn and Reiser, 1991;Hodgson and Quinn, 2002). Lund et al (2002) showed high summer water temperatures to be the cause of a heat-shock response in juvenile salmonids.…”
Section: Introductionmentioning
confidence: 99%
“…A large, hot wildfire, as a result of convectional heating and input of burning debris and ash, could conceivably increase stream water temperatures to a lethal level for coldwater salmonid fishes. This elevation of water temperature would have to be present only for a short (less than an hour) period of time (Lee and Rinne 1980). Although the recent Mt.…”
Section: Riparian-stream Ecosystemsmentioning
confidence: 99%
“…However, the life-cycle of brook trout is heavily influenced by the degree and timing of temperature changes [11,20]. High stream temperatures cause physical stress including slowed metabolism and decreased growth rate, adverse effects on critical life-cycle stages such as spawning or migration triggers, and in extreme cases, mortality [7,[21][22][23][24]. Distribution is also affected as coldwater fish actively avoid water temperatures that exceed their preferred temperature by 2-5 • C [25,26].…”
Section: Introductionmentioning
confidence: 99%